2019
DOI: 10.3390/pharmacy7030100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Use of Risperidone for Dementia in Australia Following Changed Guidelines

Abstract: Background: Risperidone is the only antipsychotic approved in Australia for the management of the behavioural and psychological symptoms of dementia (BPSD). In June 2015, the Australian Government Therapeutic Goods Administration (TGA) amended the indication to restrict use in BPSD to patients with Alzheimer’s dementia for a maximum twelve-week duration. We aimed to determine whether the rate and duration of risperidone use for BPSD decreased following the regulatory changes. Methods: we conducted a study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…These rates are higher than reported in previous studies that included older people without dementia 41 and are consistent with evidence from veteran populations where a modest decrease in dispensing over time has been reported 42 . There was also little variation between geographical regions, suggesting that high rates of antipsychotic and other sedative medicine prescribing are common across most regions of Australia.…”
Section: Discussionsupporting
confidence: 89%
“…These rates are higher than reported in previous studies that included older people without dementia 41 and are consistent with evidence from veteran populations where a modest decrease in dispensing over time has been reported 42 . There was also little variation between geographical regions, suggesting that high rates of antipsychotic and other sedative medicine prescribing are common across most regions of Australia.…”
Section: Discussionsupporting
confidence: 89%
“…Our study was conducted using administrative claims data for DVA clients (veterans and spouses), and prior research has shown that this population has comparable use of health services to other Australians of similar age and health status 32 . Seventy‐one per cent of our study population were female, which is similar to the proportion of females in aged care in other studies in the veteran population 33,34 and in the general Australian population 35…”
Section: Discussionsupporting
confidence: 87%
“…during this period. Our findings are in keeping with another population-based study which found the monthly rate of risperidone use among Australian veterans living in PRAC facilities decreased during 2012-2015, with further decreases observed immediately following changes to prescribing criteria in August 2015 47. It is important to note that data for the present study were only available to mid-2016 at the time of cohort construction and changes in the prevalence of prolonged antipsychotic use and overall duration of use may have occurred since this period.…”
supporting
confidence: 91%